EVALUASI KEANDALAN SISTEM JARINGAN DISTRIBUSI 20 KV PADA PT.PLN (PERSERO) RAYON NGABANG - ., FOLONIUS DIDO (Jurnal Teknik Elektro Universitas Tanjungpura, 2018)
The current level of reliability of a distribution system is very important in order to ensure continunity in the supplay of electric power to costumers. Therefore the need for evaluation of reliability of distribution system to see wather the system is in a state good or bad. The results of the evaluation show the value of the index on each feeder i.e feeder Tebedak , feeder Tungkul, feeder Air Besar, feeder Jelimpo feeder Munggu, feeder Senggiring 3, dan feeder Sengah Temila in a row. The value of MTTF i.e  1.094,64 ; 282,4713 ; 167,9263 ; 265,35 ; 291,6757; 32,7917 514,5635, The value of MTTR  i.e 0,36 ; 0,1093 ; 0,5352 ; 0,4327 ; 0,3243 ; 0,3901 ; 0,7306, The value of MTTBF  i.e 1.095 ; 282,5806 ; 168,4615 ; 265,7827 ; 292 ; 33,1818 ; 515,2921, The value of SAIFI i.e  0,0887 ; 0,8856 ; 0,9954 ; 0,0532 ; 0,0764 ; 3,8762 ; 0,0968,  The value of SAIDI  i.e  0,03192 ; 0,0968 ; 0,5327 ; 0,0230 ; 0,0248 ; 1,5123 ; 0,0710 ; 2,29252, The value of CAIFI  i.e 0,3695 ; 0,3428 0,4292 ; 0,0447; 0,0954 ; 2,5631; 0,0931, The value of CAIDI  i.e 0,3599 ; 0,1093 ; 0,5352 ; 0,4327 ; 0,3243 ; 0,3901 ; 0,7335. Base  on the result of the evaluation of the feeder Senggiring 3 is above the standard value of the PLN, the system can be said to be not reliable. As for the feeder Air Besar, feeder Jelimpo, Feeder Munggu, and feeder Sengah Temila are still below the standard value of PLN. Therefore it is stil considered qualite reliable. Keyword: The reliability index MTTF, MTTR, MTBF, SAIFI, SAIDI, CAIFI, CAIDI